2002
DOI: 10.1002/1099-0690(200212)2002:23<4005::aid-ejoc4005>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antileishmanial Activity of Indoloquinones Containing a Fused Benzothiazole Ring

Abstract: Pyrazinoindoloquinone 6 was synthesized by alkylation of ethyl 4,7-dimethoxyindole-2-carboxylate (1), followed by cyclization of the N-bromoethyl derivative 2b in the presence of ammonia. Oxidative demethylation of 2b and of the oxopyrazinoindole 3 with silver(II) oxide furnished quinones 5b and 6. Reduction of 3 with lithium aluminium hydride in dioxane provided 4, which was oxidized to afford 7. Quinones 5b, 6, and 7 were then treated in situ with the thiazole o-quinodimethane 9 to afford regioisomeric mixtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…Some heterocyclic quinones have been reported to be active in vitro against virulent strains of Leishmania sp. (Tournaire et al, 1996;Valderrama et al, 1999;Tapia et al, 2003a;Tapia et al, 2002b;Tapia et al, 2003b), it is why we have explored the antileishmanial activity of various quinonic compounds. We have performed in vitro tests in order to identify three-dimensional structural similarities between these compounds that may explain their potency against L. donovani, or L. major or both strains.…”
Section: Molecular Modeling Studymentioning
confidence: 99%
“…Some heterocyclic quinones have been reported to be active in vitro against virulent strains of Leishmania sp. (Tournaire et al, 1996;Valderrama et al, 1999;Tapia et al, 2003a;Tapia et al, 2002b;Tapia et al, 2003b), it is why we have explored the antileishmanial activity of various quinonic compounds. We have performed in vitro tests in order to identify three-dimensional structural similarities between these compounds that may explain their potency against L. donovani, or L. major or both strains.…”
Section: Molecular Modeling Studymentioning
confidence: 99%
“…The most common and classical method was reported as direct method that involved condensation of an ortho-amino thiophenol with a substituted aromatic aldehyde, carboxylic acid, acyl chloride or nitrile to synthesize C-2 substituted benzothiazoles, but it was found that this method is not appropriate for majority of substituted C-2 aryl benzothiazoles because the main difficulty encountered in synthesis of the readily oxidisable 2-amino thiophenols bearing substituent groups. For above said reason some other methods were reported and extensively used in the laboratories that based on the use of the potassium ferricyanide radical cyclization of thiobenzanilides 10 . This method was named as Jacobsen cyclization and popularized because it produced only one product.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, significant research has been carried out taking benzothiazole as the basic moiety. From the literature survey, it has been found that extensive work has been reported on 2-substituted benzothiazole derivatives in the past and evaluated for different activities, such as, antibacterial,[ 1 ] antiproliferative activity,[ 2 ] antiviral,[ 3 ] antitumor,[ 4 ] antifungal,[ 5 ] anti-inflammatory,[ 6 ] antioxidative and radioprotective,[ 7 ] antidiabetic,[ 8 ] antihelmintic,[ 9 ] antileishmanial,[ 10 ] anticonvulsant,[ 11 ] antimycobacterial,[ 12 ] neuroprotective,[ 13 ] and antipsychotic. [ 14 ] There are a number of pharmaceuticals and nutraceutical drugs available in the market containing benzothiazole moiety, reported to have different clinical uses.…”
Section: Introductionmentioning
confidence: 99%